Density and coverage of seagrass at Tunggul Beach, Paciran, Lamongan, East Java - Nuansa, Linggar Budi; Sawiji, Asri; Muslih, Toha (UIN Sunan Ampel Surabaya, 2021)
Seagrass is an ecosystem that has an important role as nursery and spawning ground in the life cycle in the sea. Increased human activity and climate change are feared to damage seagrass ecosystems so it is important to maintain their sustainability. This study aims to find out the composition of species, density and coverage of seagrass at Tunggul Beach, Paciran, Lamongan. This research was conducted on August until October 2020 by applying purposive sampling method as the basis for determining location point at 2 stations, with 3 substations at each station with transect line along 100 m. Seagrass data retrieval method using transect quadrant 50 x 50 cm to observe the coverage and calculate seagrass stand. The results showed the type of seagrass found on Tunggul Beach are two species, Thalassia hemprichii and Enhalus acroides. Seagrass density value at station 1 is rather tight with a density value of 92.48% and at station 2 is rare with a value of 73.09%. The percentage of seagrass coverage at station 1 indicates a solid category with a coverage value of 54.92% and in the station 2 shows a medium coverage category with a value of 31.25%.